Pengembangan Video Dokumentasi Preservasi Tari Tradisional “Denok Deblong” di Perpustakaan Menggunakan Model ADDIE - Ary Amar Haq; Roro Isyawati Permata Ganggi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
This research background is the persistent lack of appropriate cultural documentation activities. Most documentation of existing culture is generally only recorded in one direction. This causes the knowledge that exists in a culture to not be channeled effectively. The formulation of the problem in this research is how to document the Denok Deblong Folk Dance at Sanggar Greget Semarang through short videos. The aim of this research is to document the Denok Deblong Folk Dance at Sanggar Greget Semarang through short videos. The research method used is research & development (R&D). Data analysis was conducted using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. This study's results reveal that the Denok Deblong Dance documentation process involves multiple stages. First, analyse the requirements for making a short video. Second, preparing the script and other technical aspects for production. Third, developing the design of the short video that has been created. The fourth step involves the production of the short video. The fifth step involves evaluating the project using expert judgement. The involvement of expert judgement at the end of the short video production is a new approach in local cultural documentation videos, aimed at quality control and reinforcing the credibility of the information regarding the produced documentation. This sequence of stages produces a workflow to create Denok Deblong Dance documentation that is relevant and suitable for the library.